Overexpression of OsSWEET5 in rice causes growth retardation and precocious senescence. - Yong Zhou; Li Liu; Weifeng Huang; Meng Yuan; Fei Zhou; Xianghua Li; Yongjun Lin (PLoS ONE)
As a novel sugar transporter family, SWEETs play important roles in plant growth and development. Here, we characterized a SWEET gene named OsSWEET5 through its overexpression in rice. Heterologous expression assay indicated that OsSWEET5 encoded a galactose transporter in yeast. OsSWEET5-overexpressing plants displayed the phenotypes of growth retardation and precocious senescence at seedling stage. GC-MS analysis showed that the sugar levels were largely altered in the leaves of the OsSWEET5-overexpressing plants. Molecular analysis revealed that these phenotypes might be due to the transcriptional changes of the genes involved in sugar metabolism and transport. In addition, the transgenic plants showed a lower level of auxin with altered transcription of genes involved in auxin signaling and translocation pathways. However, no obvious phenotype was observed between the amiRNA-OsSWEET5 transgenic lines and WT plants, which could be a result of the functional redundancy of the galactose transporters in rice. Taken together, our findings suggest that OsSWEET5 plays a crucial role in regulating the crosstalk between sugar and auxin in rice.